Lack of bundled care intervention training program will trip up rates of ventilator associated pneumonia: the contemporary trend - Kaushal, Rituja; Gupta, Sanjeev; Saraogi, Aashish; Singh, Sandhya (International Journal Of Community Medicine And Public Health, 2019)
Background: Ventilator associated pneumonia (VAP) is the deadliest hospital acquired infection in many low resource settings of developing countries. For VAP prevention, the concept of bundle of care was defined. Evidence based resources showed it enabled great successes in VAP prevention. It has been observed in clinical practice due to insufficient compliance, there is a need to address related issues in order to define easier-to-apply procedures. Methods: It is a retrospective analytical secondary data based study. It was conducted in a tertiary care hospital of Bhopal city. Results: T value of Mann Whitney/U test was found to be statistically significant and is indicating need of “Bundle Care Intervention” training for the prevention of increase in ventilator associated pneumonia rates in any health care setting. Conclusions: Expanded bevy of options related to infect